Presidential discourse in Peru: comparative analysis and social issues in the speech of five presidents (2016-2023) - Robles Olivos, Rafael (2023)
The importance of investigating the political discourse of a country lies in understanding the intrinsic complexity of political communication directed by its leaders. Hence, the importance of expanding the previous analysis of presidential speeches in Peru, transmitted in real time through the media, which is the objective of this study. For this purpose, the time frame is delimited between 2018 and 2023, covering a linguistic corpus that exceeds 105 000 words, distributed in 60 speeches made by five political leaders. With the application of a methodology that merges the ethnography of communication and the analysis of lexical frequencies, we seek to understand the communicative dynamics, semantic values and content of these speeches. The results highlight the variability in discursive practices, evidencing a convergence in the use of key words that highlight the importance of the country and the ability of the leaders to establish representation and inclusion. In addition, the shared concern for corruption and the emphasis on health during the pandemic; the strategic relevance of certain terms in the construction of social cohesion and collective identity; as well as marked centralism in the presidential speeches analyzed are highlighted.